Serum GDF15 level as predictive biomarker of clinical outcome in patients with unresectable hepatocellular carcinoma treated with hepatic arterial infusion chemotherapy - Xing, Rui; Gan, Junyu; Mei, Jie; Li, Zhixiong; Xu, Jing (Frontiers in Immunology, 2025)
BackgroundHepatic arterial infusion chemotherapy (HAIC) using the FOLFOX regimen has been explored for unresectable hepatocellular carcinoma (HCC) patients, yet predictive biomarkers are lacking. This study aimed to evaluate the potential of serum growth differentiation factor 15 (GDF15) as a biomarker for predicting therapeutic response and survival outcomes in HCC patients undergoing FOLFOX-HAIC.MethodsPretreatment serum samples were collected from patients with unresectable HCC who received FOLFOX-HAIC between October 2016 and January 2019. GDF15 levels were measured using enzyme-linked immunosorbent assay (ELISA). Associations between serum GDF15 levels and treatment response, overall survival (OS), progression-free survival (PFS), and clinical characteristics were analyzed.ResultsA total of 150 patients were included in the study. The mean GDF15 level was 7.16 ng/mL (mean ± SEM: 7.16 ± 0.72; range: 0.39-53.55 ng/mL). High serum GDF15 levels were significantly associated with poorer treatment response, shorter OS (median: 21.1 vs 40.33 months, p = 0.0081) and PFS (median: 13.93 vs 20.47 months, p = 0.0125). Multivariate Cox proportional hazards analysis identified serum GDF15 as an independent predictor of PFS (HR, 1.521; 95% CI, 1.014-2.283; p = 0.043). Additionally, elevated GDF15 was positively correlated with larger tumor size (p < 0.0001), presence of microvascular invasion (p = 0.026) and abnormal AST levels (p = 0.001).ConclusionSerum GDF15 represents a potential prognostic biomarker in patients with unresectable HCC undergoing FOLFOX-HAIC treatment and may help guide treatment stratification.